2018
DOI: 10.4236/anp.2018.71003
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Optimization of Solution Combustion Synthesis for Pioneered La<sub>2</sub>O<sub>3</sub> Nanostructures to Application as Future CMOS and NVMS Generations

Abstract: The Present Research paper discuses the synthesis and characterization of lanthanum oxide (La 2 O 3) nanoparticles by using a very low cost Solution Combustion Method. We are using Acetamide as fuel in present method. In future, most of manufacturer of integrated circuits recently announced and introduced hafnium and lanthanum based high-κ dielectrics materials in their next CMOS generations and also Lanthanum oxides show some important applications such as luminescent devices, sensors, up-conversion materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The spectrum of the initial sample Zn4La shows a sharp band from 3604 cm −1 attributed to the OH groups from the La(OH) 3 . The wide band centered at about 3450 cm −1 is assigned to the water molecules incorporated in the solid (ν H2O ) and coexists with the deformation band (δ H2O ) from 1567 cm −1 which disappears by heating/annealing at 400 • C. The bands located at 1485 cm −1 , 855,662 cm −1 correspond to the formation of La 2 O 3 mixed with LaO (OH) [35,36]. This is supported also by the disappearance of the band from 1019 cm −1 , the modification of the bands from 1417 and 695 cm −1 , which become less intense and suffer modifications of the aspect.…”
Section: Ftir Analysismentioning
confidence: 98%
“…The spectrum of the initial sample Zn4La shows a sharp band from 3604 cm −1 attributed to the OH groups from the La(OH) 3 . The wide band centered at about 3450 cm −1 is assigned to the water molecules incorporated in the solid (ν H2O ) and coexists with the deformation band (δ H2O ) from 1567 cm −1 which disappears by heating/annealing at 400 • C. The bands located at 1485 cm −1 , 855,662 cm −1 correspond to the formation of La 2 O 3 mixed with LaO (OH) [35,36]. This is supported also by the disappearance of the band from 1019 cm −1 , the modification of the bands from 1417 and 695 cm −1 , which become less intense and suffer modifications of the aspect.…”
Section: Ftir Analysismentioning
confidence: 98%
“…La2O3 material is produced by adopting the SC method suggested by Pathan, et al [10] and the HSWC method suggested by Hojo, et al [22].…”
Section: Theoretical Synthesis Of Lanthanum Oxidementioning
confidence: 99%
“…Because of the high-quality applications of La2O3 nanoparticles in many fields, it was successfully fabricated using various chemical and physical methods. Several studies have reported on the synthesis of La2O3 by various methods, including combustion, coprecipitation, hydrothermal, sol-gel, reflux, sonochemical, solvothermal, spray pyrolysis, and thermal decomposition methods [9][10][11][12][13][14][15][16][17]. The method election for the production of lanthanum nanoparticles is based on advantages.…”
mentioning
confidence: 99%
“…Lanthanum is the rst rare earth metal that has a wide band gap, low lattice energy, and large dielectric constants [12]. Due to its unique electronic con guration lanthanum has been utilized for various applications such as MOSFET, NVM, insulator, nano-volatile memories, and catalytic elds [13].…”
Section: Introductionmentioning
confidence: 99%